1977
DOI: 10.1002/jcp.1040910305
|View full text |Cite
|
Sign up to set email alerts
|

PHA stimulation of human lymphocytes during amino acid deprivation. Protein, RNA and DNA synthesis

Abstract: Resting lymphocytes are in the Go phase of the cell cycle. Upon activation by PHA, they progress into GI with accompanying increased protein and RNA synthesis, initiate DNA synthesis and divide. We have studied the kinetics of inhibition of macromolecular synthesis during activation in the absence of single amino acids. Three types of kinetics are observed. In the absence of tryptophan or isoleucine, stimulated lymphocytes show a normal increase in protein and RNA synthesis during the first 30 hours of stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The data also provided evidence that lymphocytes stimulated in lysinedeficient medium are closer to the S phase (DNA synthesis) of the cell cycle than resting lymphocytes [6]. The results presented in the present paper show that during the early response to phytohaemagglutinin, there is a component of increased transcriptional activity which, although sensitive to cycloheximide, is unaffected by lysine deprivation and which remains stable for at least 24 h.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The data also provided evidence that lymphocytes stimulated in lysinedeficient medium are closer to the S phase (DNA synthesis) of the cell cycle than resting lymphocytes [6]. The results presented in the present paper show that during the early response to phytohaemagglutinin, there is a component of increased transcriptional activity which, although sensitive to cycloheximide, is unaffected by lysine deprivation and which remains stable for at least 24 h.…”
Section: Discussionsupporting
confidence: 67%
“…When lymphocytes are stimulated in the absence of an essential amino acid, the normal increase in the rate of RNA synthesis in response to phytohaemagglutinin does not occur [6]. Fig.3 shows the kinetics of activation of RNA polymerase I during the first 8 h of stimulation in complete medium and in medium lacking lysine.…”
Section: R N a Polymerase I Activation By Phytohaemagglutinin And Itsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous cohort studies, the BCAA-supplemented groups demonstrated elevations in the absolute lymphocyte count (9,10). In previous in vitro studies, the omission of a single BCAA from the medium of cultured lymphocytes resulted in the complete abolition of protein synthesis or proliferation (11)(12)(13). These findings simply reflect the fact that BCAA are essential cell components.…”
Section: H Epatitis C Virus (Hcv)mentioning
confidence: 87%
“…Bassit et al29 reported that BCAA supplementation restored the ability of peripheral blood mononuclear cells to proliferate in response to mitogens after long‐distance intensive exercise. Meanwhile, in vitro studies30‐32 have shown that the omission of a single BCAA from a medium of cultured lymphocytes completely abolishes protein synthesis and cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%